P85. Biased processing of social information in psychogenic nonepileptic seizures. Issue 8 (August 2015) - Schönenberg, M.; Höhnle, N.; Jusyte, A.; Mayer, S.; Weber, Y.; Schell, C.
<x xml:space="preserve">Abstract</x> The pathogenesis of psychogenic nonepileptic seizures (PNES) has been frequently related to specific psychological factors and personality traits. In particular, disturbances in emotion perception and affect regulation are supposed to trigger seizure-like episodes in these patients. However, less is known how PNES individuals process and interpret affective information and how this (inadaequate) information processing can affect vulnerability towards their attacks. Thus, the present study aimed to investigate basal facial affect recognition as well as higher-order cognitive mind-reading skills in order to further investigate specific perceptual and cognitive biases in the processing of social affective information in a homogenous sample of patients suffering from PNES. In the present study we assessed alexithymia via self-report in a sample of patients diagnosed with PNES and matched healthy controls. Affect perception was tested using a series of computerized movies of models whose facial expressions slowly change from neutral to full-blown emotion (anger, fear, sadness, happiness, disgust, and surprise), allowing a fine-grained assessment of facial emotion recognition impairments. Further, we presented all participants with the Movie for the Assessment of Social Cognition, a well-validated video-based test for the evaluation of subtle mind-reading deficits that permits the separate quantification of the use of aberrant mentalizing strategies like 'overmentalizing' and 'undermentalizing' related to affective and cognitive dimensions. We predicted that PNES patients would show deficits in both, affect perception and mentalizing. The first preliminary data analyses revealed increased alexithymic traits and specifically impaired mentalizing skills in PNES individuals, while basal facial expression recognition appeared to be intact in these patients. In summary, our findings suggest that patients suffering from PNES exhibit deficits in mind-reading abilities, but do not show impairments in basal facial affect recognition. More specifically, PNES individuals show a tendency to over-attribute inappropriate affective states to others, which could be the consequence of the inability to adequately experience and express their own emotional reactions. Hence, these patients might benefit from psychotherapeutic interventions that focus on the disturbed affect regulation and aim to enhance emotional awareness.